Discussion: "Radial strain behaviors and stress state interpretation of soil under direct simple shear" by X. Kang, Y. Cheng, and L. Ge. - Li, Y.; Yang, Y.M.; Roberts, G.W.; Yu, H.S. (ASTM International, 2017)
Two methods were used in determining the stress state of simple shear tests in the discussed paper. The authors stated that the second method was proposed by Oda and Konishi, based on the distribution law of contact force (Oda, M. and Konishi, J., “Rotation of Principal Stresses in Granular Material During Simple,” Soils and Foundations., Vol. 14, No. 4, 1974, pp. 39–53.). However, the relation used in the method was found by Roscoe et al. from experimental results (Roscoe, K. H., Bassett, R. H., and Cole, E. R. L., “Principal Axes Observed During Simple Shear of a Sand,” Proceedings of the Geotechnical Conference on Shear Strength Properties of Natural Soils and Rocks, Vol. 1, Norwegian Geotechnical Institute, Oslo, 1967, pp. 231–237.). In addition, the determination of the constant k, which used k = 1 − K0, was problematic in the discussed paper. First, the equation could only be deduced after some assumptions were made. Second, the value of k was not a constant if the K0 changed.